Soil water retention and s index after crop rotation and chiseling - Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP] (Sociedade Brasileira de Ciência do Solo, 2011)
Soil compaction can be minimized either mechanically or biologically, using plant species with vigorous root systems. An experiment was carried out with soybean (Glycine max) in rotation with triticale (X Triticosecale) and sunflower (Helianthus annuus) in fall-winter associated with pearl millet (Pennisetum glaucum), grain sorghum (Sorghum bicolor) or sunn hemp (Crotalaria juncea) in spring. Crop rotation under no-till was compared with mechanical chiseling. The experiment was carried out in Botucatu, São Paulo State, Brazil. Soil quality was estimated using the S index and soil water retention curves (in the layers of 0-0.05, 0.075-0.125, 0.15-0.20, 0.275-0.325, and 0.475-0.525 m deep). Crop rotation and chiseling improved soil quality, increasing the S index to over 0.035 to a depth of 20 cm in the soil profile. The improved soil quality, as shown by the S index, makes the use of mechanical chiseling unnecessary, since after 3 years the soil physical quality under no-tilled crop rotation and chiseling was similar.

A compactação do solo pode ser corrigida mecanicamente ou usando espécies vegetais com sistema radicular vigoroso. Um experimento foi conduzido com soja (Glycine max) em rotação com triticale (X Triticosecale) e girassol (Helianthus annuus) cultivados no outono/inverno, associados com milheto (Pennisetum glaucum), sorgo (Sorghum bicolor) ou crotalária (Crotalaria juncea) cultivados na primavera. Rotações sob semeadura direta foram comparadas com um tratamento com escarificação no início do experimento. A qualidade do solo foi estimada usando-se o índice S e as curvas de retenção de água do solo nas profundidades de 0-0,05, 0,075-0,15, 0,15-0,20, 0,275-0,325 e 0,475-0,525 m. As rotações de culturas e a escarificação melhoraram a qualidade do solo, aumentando o índice S acima de 0,035 até 0,20 m no perfil do solo. Entretanto, a melhoria na qualidade do solo, conforme determinada por meio do índice S, não justifica o uso de escarificação mecânica, uma vez que as parcelas sob rotação de culturas em semeadura direta mostraram qualidade física do solo semelhante após três anos.
Retenção de água no solo e índice s influenciados por rotação de culturas e escarificação
Keywords: cropping systems; soil compaction; tillage; soil quality